Identificação das dificuldades na definição de questões de valor para os Stakeholders em Obras Públicas Padronizadas com Base no Target Costing - Lima, Renan Tenório de Araújo (2019)
The public works enterprises have peculiarities compared to private civil construction case. These come from the high number of stakeholders related to the projects, as well as legal issues related to the application of public money. In this sense, there are few studies relating questions of attendance to the needs of these stakeholders, even if we observed advances in the constructive techniques employed in the sector. Hence, enterprises that do not meet the needs of stakeholders are observed, mainly due to the lack of sufficient information in the design phases about these stakeholders. This research focused on the Brazilian Federal Government construction program of children day care centers, called PROINFÂNCIA. Assuming that one of the roots of the problems encountered in the design lies in the definition of who the stakeholders are and what their need, the research adopted a target costing approach in the management of the value perception of the involved parties, adding necessary ideas to these definitions. In addition, post-occupation evaluation tools were used, due to the phase of the projects that served as the research object. Thus, the objective of this research was to identify the difficulties in defining and addressing issues of value to the stakeholders of public works with standardized design, based on the target costing theory. The preliminary phase of the research comprises an initial bibliographical review to choose the research line to be delineated, as well as a systemic mapping of the target costing literature, relating the subject to public works. Next, the search method was chosen. The study included multiple case studies with application of semi structured forms to various parties involved in completed and running buildings in the Brazilian State of Sergipe. The forms were prepared according to the literature review. Most questions have their responses on a Likert scale, complemented by interview, constituting a qualitative-quantitative research method. As a result, there is a high level of complexity in the definition of clients, as well as difficulties in answering questions of value to the research participant stakeholders. In conclusion, the tools proposed by target costing and value engineering, as well as those of the lean philosophy, present practical solutions to several of the problems found in the projects throughout the research.